The Effects of Salvianolate Combined With Western Medicine on Diabetic Nephropathy: A Systematic Review and Meta-Analysis - Yuehong Shen; Shulin Wang; Yuanyuan Liu; Ling Ge; Lili Xia; Xiaoxiao Zhang; Yuying Miao; Jianping Shen; Qian Zhou (Frontiers Media S.A., 2020)
BackgroundSalvianolate, a compound mainly composed of salvia magnesium acetate, is extracted from the Chinese herb Salvia miltiorrhiza. Because of its biological activity, easy quality control and certain efficacy, salvianolate is widely used in treating ischemic cardiocerebral vascular disease, liver damage, renal injury, diabetes, and its complications. Particularly, it has potential protective effects on diabetic nephropathy (DN).ObjectiveThis meta-analysis aimed to evaluate the efficacy and safety of salvianolate when combined with western medicine in patients affected with DN.MethodsWe searched Pubmed, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data knowledge service platform (Wanfang Data), Chinese Scientific Journal Database (VIP), and China Biology Medicine Disc (SinoMed) for randomized controlled trials (RCTs) of salvianolate in combination with western medicine on DN, including results from the foundation of each database until November 30, 2019. Two reviewers independently performed literature screening, data extraction, and quality evaluation. This meta-analysis was carried out using RevMan5.3 software.ResultsFrom the 12 RCTs, 1,030 patients from China were involved. Compared with single-use western medicine, the combination of salvianolate and western medicine for the treatment of DN could reduce levels of serum creatinine (Scr) [MD=−16.53, 95% CI (−28.79, −4.27), P=0.008], blood urea nitrogen (BUN) [MD=−1.40, 95% CI (−2.17, −0.62), P=0.0004], urinary albumin excretion rate (UARE) [SMD=−1.84, 95% CI (−2.70, −0.98), P < 0.0001], 24-hour urinary protein (24h Upro) [MD=-0.37, 95% CI (-0.47, -0.26), P < 0.00001], albumin-to-creatinine ratio (ACR) [SMD=-1.43, 95% CI (-2.64, -0.23), P=0.02], hypersensitive C-reactive protein (hs-CRP) [MD=−5.69, 95% CI (−7.09, −4.29), P < 0.00001], interleukin-6 (IL-6) [MD=−12.53, 95% CI (−18.55, −6.52), P < 0.0001], malondialdehyde (MDA) [SMD=−2.05, 95% CI (−3.67, −0.43), P=0.01], as well as improve clinical efficacy [RR=1.21, 95% CI (1.12,1.31), P < 0.00001], and increase superoxide dismutase (SOD) levels [SMD=1.12, 95% CI (0.86,1.38), P < 0.00001]. No increase in the occurrence of serious adverse events were observed in the treatment group compared with the control group.ConclusionThis study indicated that salvianolate combined with western medicine contributes to protecting renal function, inhibiting inflammation, and exhibiting anti-oxidative properties, thereby improving clinical efficacy. Thus, salvianolate can be considered as a potential complementary therapy for DN patients. However, due to the low quality of methodology and small sample sizes, more rigorous and larger trials are essential to validate our results.